(untitled) (Journal of Libya for geographical studies, 2025)
This study aimed to analyze the effects of economic rent, specifically in the oil sector, on the productive sectors of the Libyan economy. It examined the impact of an inflated labor force in the services sector, alongside the decline in the contribution of productive sectors—particularly agriculture and industry to the gross domestic product (GDP).To achieve the research objectives, the study relied on reviewing academic sources and previous studies that addressed the subject from multiple perspectives, in addition to analyzing official statistics and reports issued by relevant authorities. The research methodology incorporated historical, descriptive analytical, and comparative approaches to collect, interpret, and compare pertinent data and information. The study concluded that a rentier economy leads to economic instability, as it is directly influenced by fluctuations in global oil prices and the political crises faced by oil exporting countries. Oil revenues have had a clear impact on Libya’s labor structure, with a significant contraction in the productive sector and notable growth in the services sector. During the 1970s, the growth rate of the workforce in productive sectors recorded a negative rate of 14%, whereas the services sector experienced a 35% increase in the same period. Furthermore, the findings indicated that oil rent has accounted for more than 50% of the GDP in most years since its discovery, adversely affecting non-oil sectors. In 2008, these sectors recorded their lowest contribution to the national GDP, amounting to only 21.8% of the country’s total output If you need any refinements or further improvements, I’m happy to assist!